Isolation, Identification, and Resistance Test of Escherichia coli to Antibiotics in Ujung Berung Broiler Poultry - Afifa Kantamaryana, Fatia Nasyna; Balia, Roostita L; Putranto, Wendry Setiyadi (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
Escherichia coli is commensal bacteria in the intestinal of broiler chickens with low virulence. However, mostly pathogenic and cause colibacillosis illness. Inappropriate use of antibiotics in broiler chickens has been widely reported. This research aims to determine the presence of E. coli contamination in the poultry environment and determine the levels of antibiotics resistance of erythromycin, doxycycline, oxytetracycline and neomycin. The research was carried out through isolation and identification of E. coli using EMB media, Gram staining, and biochemical tests. Then, an antibiotic resistance test was carried out using by Kirby-Bauer method. From a total of 10 samples (3 coops), 7 (70%) were positive for E. coli. The positive of 7 which for E. coli, 43% of the isolates came from fresh feces obtained from coops 1, 2, and 3; 43% of the isolates came from litter from coops 1, 2, and 3; and 14% of isolates from soil outside the coop 3. The antibiotic resistance results by Kirby-Bauer method showed that E. coli was 100% resistant to erythromycin, 100% to neomycin, 66.7% to doxycycline, and 66.7% to oxytetracycline throughout isolates from feces and litter. Other results showed that isolates from soil outside coop 3 showed resistance to all antibiotics. Taken together, we concluded the E. coli has been contamination which is proven by antibiotic resistance.